2018
DOI: 10.1016/j.mattod.2018.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Recent progresses on physics and applications of vanadium dioxide

Abstract: As a strongly correlated electron material, vanadium dioxide (VO 2) has been a focus of research since its discovery in 1959, owing to its well-known metal-insulator transition coupled with a structural phase transition. Recent years have witnessed both exciting discoveries in our understanding of the physics of VO 2 and developments in new applications of related materials. In this article, we review some of these recent progresses on the phase transition mechanism and dynamics, phase diagrams and imperfectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
266
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 398 publications
(269 citation statements)
references
References 237 publications
(435 reference statements)
2
266
0
1
Order By: Relevance
“…Further discussion, which will be given in the third section, proves that this variation is different from a mere thermal effect. After excluding the magnetic contribution of VO 2 single layer (Figure S1c, Supporting Information), it is reasonable to believe that the effect is mainly caused by the phase change of VO 2 ‐induced modulation on NiFe. It is noteworthy that the phase change temperature of VO 2 can be tuned from 300 to nearly 400 K by methods like doping or substrate stress, which will benefit its device application …”
Section: Magnetism Modulation Induced By Vo2 Phase Changementioning
confidence: 99%
“…Further discussion, which will be given in the third section, proves that this variation is different from a mere thermal effect. After excluding the magnetic contribution of VO 2 single layer (Figure S1c, Supporting Information), it is reasonable to believe that the effect is mainly caused by the phase change of VO 2 ‐induced modulation on NiFe. It is noteworthy that the phase change temperature of VO 2 can be tuned from 300 to nearly 400 K by methods like doping or substrate stress, which will benefit its device application …”
Section: Magnetism Modulation Induced By Vo2 Phase Changementioning
confidence: 99%
“…[50][51][52][53][54][55] The IMT results in an electrical conductivity change of three to four orders of magnitude together with a lattice structure transformation from a monoclinic to a tetragonal state (Figure 1a). [56][57][58] Various IMT triggering mechanisms, such as thermal heating, electrical bias application, and optical excitation, can provide a wide range of tunable devices. [59][60][61][62][63] During the IMT, the THz conductivity of VO 2 varies by several orders of magnitude.…”
Section: Vanadium Dioxidementioning
confidence: 99%
“…Alternately, Zylbersztejn and Mott attributed the MIT to the Mott–Hubbard model by considering the strong electron–electron correlations, and concluded that the MIT would happen when the electron density ( n e ) and Bohr radius ( a H ) satisfy n e 1/3 a H ≈ 0.2 . As summarized in the most recent review, the physical nature of the MIT remains a long standing debate, and the difficulty in assigning the relative importance of each mechanism lies in the challenge of decoupling the structural and electronic portions of the ultrafast phase transition. Indeed, it is difficult to understand the MIT of VO 2 completely using only one model, and the cooperation of these two mechanisms is strongly supported by considering the phase transition kinetics and the mechanism may also vary by different stimuli.…”
Section: Introductionmentioning
confidence: 99%